Cancer incidence and mortality and state of cancer care for colorectal cancer patients in the Russian Far East - V. P. Gordienko; A. S. Ilyushenok (Сибирский онкологический журнал)
The aim of the study was to estimate the incidence and mortality rates in patients with colorectal cancer in the Russian Far east in the time period from 2008 to 2020. Material and methods. Cancer incidence and mortality data collected from population-based cancer registries were used. Results. In 2020, the average rate of colorectal cancer incidence in the Russian Far east was 15.29 ± 0.33 per 100,000 men (2019: 15.35 ± 0.36) with an annual percent decrease of 5.40% since 2008. The corresponding rate increased to 12.92 ± 0.23 (2019: 12.98 ± 0.25) per 100,000 women with an annual percent increase of 5.95 %. By the end of the study period the number of new cancer cases increased to 13.2 % (2008: 1.3 %). The percent of morphological confirmation of the diagnosis was lower than in the Russian Federation as a whole (93.4 % versus 96.0; 2008: 84.3 %). The number of patients followed-up for 5 and more years was lower than in the Russian Federation as a whole (52.7 % versus 55.0 %; 2008: 41.9 %). The quality of the cancer service activity was marked by the index of reliability of registration, which was not lower than 0.40 in any of the territories of the district. The average colorectal cancer mortality rate in men was 8.73 ± 0.12 per 100,000 population (2019: 8.72 ± 0.13), which exceeded that in women (6.83 ± 0.10; 2019: 7.37 ± 0.53). The death rate within the first year after diagnosis decreased to 25.0 % (2008: 34.3 %). Conclusion. Unfortunately, the work of primary healthcare organizations responsible for early detection of cancer has not led to significant changes in the incidence rates. (2020: 13.02 0/0000; 2008: 12.9858 0/0000) and mortality rates (2020: 7.4558 0/0000; 2008: 7.6158 0/0000). Cancer screening programs aimed not only at the early cancer detection, but also at the formation of groups being at high risk of cancer are necessary for improving cancer care in the Russian Far east region. These programs should be accompanied by the training of professional staff and the development of modern diagnostic and treatment regimens.